Organization and methodology of management accounting at large enterprises - A.R. Shumska; I.V. Shnyr (Економіка, управління та адміністрування)
Modern realities of doing business force entrepreneurs to form an internal management information base that makes it possible to monitor all stages in the formation of the final consumer product promptly. The main system of construction, methodology, and organization of management accounting at large enterprises has been formed, which will allow for effectively improving the economic position of the enterprise, and to analyze relevant information from the point of view of the importance of the decisions made. A similar system of organization of management accounting is implemented by observing the main stages of implementation of management accounting at large enterprises. When creating management accounting at enterprises, the peculiarity of the type of economic activity of the enterprise, the seasonality of production, analysis of the staffing of the enterprise, and other factors are considered. The separation of management accounting as a separate unit of accounting in large enterprises contains correspondence to a certain «supporting skeleton» of the construction of the management accounting system. The presented method of successful display of management accounting can be freely applied when implementing management accounting at any enterprise. The use of demand among outsourcing firms that provide management accounting services among enterprises is not excluded. The distribution of responsibilities between the manager and the management accounting specialist will allow to clearly illustrate important aspects that should be paid attention to when forming management accounting at large enterprises.